(untitled) (Cadernos de Sociomuseologia, 2019)
For an architecture in the service of contemporary museology A new generation of Museums organize and define their programs and targeted activities as a resource for development. They are concerned about the problems of the society in which they live, by promoting employment, fomenting new forms of tourism, revitalizing and creating new industries and reinforcing identities. Every day museums seek different forms of sustainability and are attentive to the promotion of human development and social and economic cohesion, demanding a new spatial organization. For these museums it will be obviously to seek a new architectural approach that takes account of the new museological realities. This is certainly the greatest challenge of contemporary architecture. Stop thinking only about traditional museums and develop a new approach to museums that are organized based on other concepts. Keywords: Architecture, Museology, Sociomuseology, Social Museology